2013
DOI: 10.3233/hab-130265
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of murine monoclonal antibody against synthetic peptide of CD34

Abstract: This antibody is highly specific and functional in biomedical applications such as ELISA, flowcytometry, immunofluorescence, and western blot assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Peptide Abs to cell surface markers are often used at fluorescent conjugates in fluorescence microscopy for IHC or flow cytometry (FC) for cells in suspension [63][64][65]143].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide Abs to cell surface markers are often used at fluorescent conjugates in fluorescence microscopy for IHC or flow cytometry (FC) for cells in suspension [63][64][65]143].…”
Section: Applicationsmentioning
confidence: 99%
“…Peptide Abs are used for numerous research purposes as well. For example, peptide Abs are often used for detecting cell surface markers, e.g., CD3, CD8, CD14, CD20, and CD34 in FC [63][64][65]143].…”
Section: Applicationsmentioning
confidence: 99%
“…Therapeutic antibodies are significant drugs for the treatment of autoimmune diseases and infections. Furthermore, antibodies are important substances in diagnostic and medical researches including therapeutic effects [9,10] they are a combination of monoclonal Abs produced against different epitopes of antigens and have great avidity to polyvalent antigens [11,12]. Sheeppox virus, Goatpox viruses, and Lumpy skin disease viruses are surprisingly alike to one another, sharing 97% nucleotide identity and studies also revealed that Sheeppox virus and Goatpox viruses share about 96% nucleotide identity over their entire length [13].…”
Section: Discussionmentioning
confidence: 99%
“…The mAbs have several applications including Cancer Immunotherapy, 91 , 94 Bone Marrow and Organ Transplantation, 95 , 96 Protein Purification, 97 - 99 Disease Diagnosis in immunoassay tests including enzyme-linked immune sorbent assay (ELISA), western blotting, immunohistochemistry and immunofluorescence tests. 100 , 101 Our team has been developed the mAbs against a wide range of antigens including TNF-α, 102 CD20, 103 CD34, 104 , 105 receptor tyrosine kinase-like orphan receptor proteins, 106 human epidermal growth factor receptor, 107 heat shock protein 70, 108 vascular endothelial growth factor receptor 2, 77 , 78 human IgG and IgA. 109 , 110 …”
Section: Monoclonal Antibodiesmentioning
confidence: 99%